2021
DOI: 10.1039/d1cc03807a
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-responsive Z-scheme system for photocatalytic lignocellulose-to-H2 conversion

Abstract: Z-scheme system was successfully constructed for visible light driven photocatalytic H2 production from lignocelluloses, the highest H2 evolution rate of this Z-scheme system achieves 5.3 and 1.6 μmol•h-1 in α-celluloses...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Because the traditional enzyme fermentation technique for convert lignocelluloses into energy substances (such as alcohol, etc.) is limited by low conversion efficiency and high purification costs, the exploration of an efficient strategy for lignocellulose-to-fuel conversion is believed to be critical for the utilization of lignocelluloses. Photocatalytic H 2 production from lignocelluloses using solar energy to drive the lignocelluloses to react with water, that is (C 6 H 10 O 5 ) n + 7 n H 2 O = 6 n CO 2 + 12 n H 2 , provides a clean and promising approach to converting lignocelluloses into chemical fuel. Since the first report by Kawai and Sakata on the photocatalytic conversion of carbohydrate into H 2 using Pt- and RuO 2 -coloaded TiO 2 as the photocatalyst, great efforts have been adopted to develop a highly efficient lignocellulose-to-H 2 conversion system, but the lignocellulose-to-H 2 conversion performance is still low. The main reason for the low performance could be related to the complicated structure and high inertness of lignocellulose, and the oxidation and decomposition of lignocelluloses are considered to be the rate-determining step for all photocatalytic lignocellulose-to-H 2 conversion processes. Recent studies have reported that lignocelluloses can be oxidized by the photogenerated holes in the valence band (VB) of a semiconductor photocatalyst when there is strong binding effect exhibited between lignocelluloses and the photocatalyst.…”
mentioning
confidence: 99%
“…Because the traditional enzyme fermentation technique for convert lignocelluloses into energy substances (such as alcohol, etc.) is limited by low conversion efficiency and high purification costs, the exploration of an efficient strategy for lignocellulose-to-fuel conversion is believed to be critical for the utilization of lignocelluloses. Photocatalytic H 2 production from lignocelluloses using solar energy to drive the lignocelluloses to react with water, that is (C 6 H 10 O 5 ) n + 7 n H 2 O = 6 n CO 2 + 12 n H 2 , provides a clean and promising approach to converting lignocelluloses into chemical fuel. Since the first report by Kawai and Sakata on the photocatalytic conversion of carbohydrate into H 2 using Pt- and RuO 2 -coloaded TiO 2 as the photocatalyst, great efforts have been adopted to develop a highly efficient lignocellulose-to-H 2 conversion system, but the lignocellulose-to-H 2 conversion performance is still low. The main reason for the low performance could be related to the complicated structure and high inertness of lignocellulose, and the oxidation and decomposition of lignocelluloses are considered to be the rate-determining step for all photocatalytic lignocellulose-to-H 2 conversion processes. Recent studies have reported that lignocelluloses can be oxidized by the photogenerated holes in the valence band (VB) of a semiconductor photocatalyst when there is strong binding effect exhibited between lignocelluloses and the photocatalyst.…”
mentioning
confidence: 99%
“…This strategy has been considered as a green and potential method for the production of H 2 from lignocellulosic biomass. [12][13][14][15][16][17][18][19][20] In this photocatalytic system, the photogenerated electron in the conduction band (CB) of the photocatalysts can reduce H + to H 2 and the residual holes in the valence band (VB) of the photocatalyst can oxidize lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these photocatalysts with a specific group or species, the • OH radical with high reactivity generated by reaction of photogenerated holes in the valence band (VB) of photocatalysts with OH − was recognized as the critical intermediate for the decomposition of lignocelluloses. 14,15 Because of the harsh thermodynamic requirements for • OH generation, only some wide-gap semiconductors were demonstrated to be active photocatalysts for photocatalytic lignocellulosic biomass-to-H 2 conversion. Very recently, we reported the use of (001) facet exposed ultrathin anatase TiO 2 nanosheets as a highly active photocatalyst for photocatalytic H 2 production from lignocellulose.…”
Section: Introductionmentioning
confidence: 99%